Revitalising metallic materials: a path towards a sustainable circular economy - Ashraf, Farhan; Lodh, Arijit; Pagone, Emanuele; Castelluccio, Gustavo M. (MDPI, 2023)
Improving materials’ productivity and reusability can advance circularity by reducing extraction and enabling efficient fully recyclable parts and systems. However, the pursuit of circular materials often focuses on the choice among reusing, repairing, or recycling materials, with limited consideration for techniques that can proactively revitalise materials. Consequently, the adoption of preventive material therapies remain relatively scarce and unexplored. This work discusses the potential for revitalising metallic materials with preventive maintenance prior to detectable damage and we identify techniques that can effectively prolong the structural lifespan of metallic components. By analysing the literature and considering the eco-footprint and implementation feasibility within the aerospace sector, this study ranks approaches based on their circularity impact and provides valuable insights to guide future research in the field of materials maintenance.
Keywords: product circularity; circular economy; maintenance